Support for My Video is Support for Me: A YouTube Scoping Review of Videos Including Adolescents With Chronic Pain. Issue 5 (May 2019) - Forgeron, Paula A.; McKenzie, Emily; O'Reilly, Jenna; Rudnicki, Erika; Caes, Line
Abstract : Objectives: Adolescents are heavy users of social media as a venue to share experience and obtain information. Adolescents with chronic pain may be no different. Given that adolescents with chronic pain report feelings of social isolation, of being different, and lack peer understanding, social media may help them obtain social support. We conducted a scoping review of YouTube to identify how adolescents with chronic pain use this platform to connect with other adolescents. Materials and Methods: The terms "youth with chronic pain" and "teens with chronic pain" were entered into the YouTube search bar to locate videos. Videos in English, targeted at and including an adolescent with chronic pain were included. Videos were screened for eligibility until 20 consecutive videos listed on the main page were excluded. For each included video the first 5 related videos suggested by YouTube in the sidebar were also screened for eligibility. Results: This selection process resulted in 18 included videos, with a total of 936 viewer comments. Recurring comment themes were identified using qualitative content analysis. Video content mainly covered multidisciplinary treatment options, alternative treatments, and impact of pain on daily life. Although a variety of treatment options were discussed, details of treatment were lacking. Comments reflected the overarching message "you are not alone!" and mainly focused on providing and receiving support, sharing suffering, and revealing the impact of pain on relationships and daily life. Discussion: Despite potential challenges associated with social media, YouTube may be a promising platform for provision of social support for adolescents with chronic pain. Abstract : Supplemental Digital Content is available in the text.